Review of Cancer among Circumpolar Indigenous Peoples. Summary Report to the Sustainable Development Working Group - Young, Kue (Sustainable Development Working Group (SDWG), 2015)
Cancer is a growing health problem among circumpolar Indigenous peoples and effective prevention and control measures require valid and reliable surveillance data to support planning and evaluation. While circumpolar countries have well-established national cancer registries, few have the capability to distinguish Indigenous from non-Indigenous peoples among cancer cases in their databases. This Arctic Council sponsored project, Cancer among Indigenous Populations in Circumpolar Regions, was approved by the Sustainable Development Working Group (SDWG) and Senior Arctic Officials in Whitehorse, Yukon, Canada, in October 2013. Project co-leads are the cochairs of SDWG’s Arctic Human Health Expert Group (AHHEG) – Prof. Kue Young, University of Alberta School of Public Health, Canada, and Leanna Ellsworth/Dianne Kinnon, Inuit Circumpolar Council, as well as the Arctic Council member states Canada and Kingdom of Denmark. Arctic Council